Study of the AISI 52100 Steel Reuse Through the Powder Metallurgy Route Using High Energy Ball Milling - Bruna Horta Bastos Kuffner; Gilbert Silva; Carlos Alberto Rodrigues; Geovani Rodrigues (Materials Research, 2017)
The AISI 52100 is a tool steel used in industry to produce bearings. After the end of its life cycle, it is remelted or discarded in deposits. The powder metallurgy rises as an alternative to recycle this material without any waste. The steps used to produce the AISI 52100 steel by powder metallurgy included: Machining with speed of 45 rpm, high energy ball milling of the scraps during 30 hours with mass/sphere relation of 1:15 and speed of 400 rpm, uniaxial pressing using 175 MPa and sintering through 30 minutes at 1200ºC. Also, were incorporated 1%, 3% and 5% of alumina particles in the milling process to increase the milling efficiency and mechanical strength after sintering. The results of microstructural and mechanical analysis indicated that the alumina addition during the milling process increased the AISI 52100 steel properties, being 3% the percentage proved as the most efficient among all additions.